Design of tangential entry swirl burner - Mohamad Faisal B Abd Rahim (School of Materials Engineering, University Malaysia Perlis, 2016)
Cooking is the process of preparing food by applying heat. Cooks select and combine ingredients using a wide range of tools and methods. In the process, the flavour, texture, appearance, and chemical properties of the ingredients can change. Although cooking results in the loss of some nutrients, it can also convert other nutrients into a form that would otherwise not be used by our bodies. Cooking also produces the desired texture and flavour we want in our food. Research has shown that cooking certain meats at high temperatures creates chemicals that are not present in uncooked meats. A few of these chemicals may increase cancer risk. This is mostly due to random temperature and heating. By using steam as the heating element, uniform heating can be obtained and maintained. Steam only exists at one temperature at one given pressure. For example at 1 bar pressure steam exist at 100C temperature and at 2 bar steam exist at 121.2C. The design of the cooking chamber is rectangular and has two chambers, interior and exterior. The steam within the exterior chamber will pass its heat through by conduction to the interior wall. The steam used is at 2 bar pressure and 121.2C. The pressure and temperature is maintained throughout the experiment, the time and the type of food cooked were the only parameters that were changed during the experiment. The result shows that different food type requires different time to cook, this is because the pressure and temperature of steam used is 2 bar and 121.2C, through conduction only 81C can be obtained within the interior chamber. Some food requires higher temperature to cook faster. To reduce the time of cooking a higher pressure and temperature steam could be used.